Microbial diversity, functional attributes, and nutritional proficiency of yogurts produced in Bangladesh - Md. Tanvir Islam; M. Shaminur Rahman; Susmita Roy Chowdhury; Tanay Chakrovarty; S. M. Kador; Md. Mazharul Islam; Khondoker Tanjim Islam; Mohammad Imtiaj Uddin Bhuiyan; Ovinu Kibria Islam (Discover Food)
Abstract Bangladeshi yogurt is a creamy, tangy dairy product with culinary significance in Bangladesh, often consumed alone or as a complement to spicy dishes. This study investigates the microbial diversity and nutritional composition in 38 samples, spanning commercial and locally produced varieties from eight districts. Through 16S rRNA amplicon sequencing, 650 Operational Taxonomic Units (OTUs) were identified: sour yogurt contained 493 OTUs, and sweet yogurt 441 OTUs. Firmicutes were predominant across both yogurt types, with unique appearances of Gracilibacteria, Gemmatimonadetes, and Spirochaetes in sour yogurt, while Euryarchaeota and Lentisphaerae were found only in sweet yogurt. Streptococcus and Lactobacillus emerged as the most abundant genera, with local sour samples presenting lower Firmicutes levels (84.98%) compared to commercial types (> 99.27%). Among the samples, those from Cox's Bazar exhibited the greatest bacterial diversity. Nutritional assessments revealed that branded yogurts were denser in nutrients, especially solids-not-fat (SNF), total solids, and essential minerals like iron and zinc. In contrast, local yogurts contained higher fat and lower sodium, appealing to consumers favoring richer textures with less salt. Increased acidity in local varieties also matched preferences for tangier flavors. Physicochemical analysis identified a negative association between Lactobacillus levels and pH, while higher fat content reduced overall bacterial diversity except for Lactobacillus, which further decreased mineral bioavailability. Carbohydrate metabolism was dominant in both types, with increased amino acid metabolism (11.72%) and xenobiotics biodegradation (3.94%) in sour yogurt. This study underscores the health-promoting properties of Bangladeshi yogurt, highlighting its unique regional microbiological and biochemical characteristics.